Overview of malignant soft-tissue sarcomas of the limbs. Issue 12 (December 2021) - Renn, A.; Adejolu, M.; Messiou, C.; Bhaludin, B.; Strauss, D.C.; Thway, K.; Moskovic, E.
Abstract : Although soft-tissue masses are common, sarcomas are rare malignant neoplasms showing variable mesenchymal differentiation and can occur at any anatomical site. Limb soft-tissue sarcomas (STS) are rare, but often lethal tumours. Although there are scores of historical pathological subtypes, this article will deal with the commonest: liposarcoma, leiomyosarcoma (LMS), undifferentiated pleomorphic sarcoma (UPS), synovial sarcoma, myxofibrosarcoma, malignant peripheral nerve sheath tumour (MPNST), epithelioid sarcoma, alveolar rhabdosarcoma, angiosarcoma and radiation-induced sarcoma (RIS). Following a review of >4, 000 adult patients with limb sarcoma from our specialist soft-tissue tumour database, we summarise the literature and their imaging findings, with emphasis on radiological hallmarks that can aide in diagnosis and management. Increased awareness of sarcoma when challenged with a new mass in the extremity can ensure timely and appropriate treatment.